KEADILAN TANPA INTEGRASI: KRITIK ATAS FRAGMENTASI EPISTEMOLOGIS DAN KEGAGALAN TRANSFORMASI SOSIAL DALAM PERSPEKTIF TEOLOGIS–HUMANISTIK - Laily Sa'adah; Rafi Maulana Taufikul Hikam; Jinani Firdausiyah; Ali Hasan Siswanto (El-Mubarak: Islamic Studies Journal, 2026)
Justice is a fundamental concept in theological, philosophical, and social traditions, yet contemporary reality demonstrates a significant gap between normative ideals and empirical practice. The background to this research problem stems from the phenomenon of structural injustice that persists amidst the advancement of modernity, which actually demonstrates the failure of value-based social transformation. This research gap lies in the epistemological fragmentation between the approaches of Islamic theology, the philosophy of justice, Sufism, and humanistic-existential psychology, which have developed fragmentarily without an integrative synthesis. This research employs an interdisciplinary theoretical approach that integrates the concept of al-'adl in Islam, philosophical justice thinking, the spiritual dimension of Sufism, and the perspective of humanistic-existential psychology. The method employed is qualitative-conceptual, with critical analysis and synthesis of classical and contemporary literature. The article's main argument asserts that the failure to realize justice is not solely a structural issue but also caused by an epistemological crisis and the loss of the spiritual dimension and human subjectivity. As a scientific contribution, this study proposes the Integrative Justice Framework (IJF) as a new conceptual model that connects theological, philosophical, spiritual, and psychological dimensions within a single holistic framework. This model is expected to bridge the gap between values ​​and practice and serve as a foundation for more just and sustainable social transformation.